2020 healthcare workers flu vaccination during covid-19: the experience of Udine University Hospital. (20th October 2021) - Chirico, L; Moretti, V; Valdi, G; Varadi, G; Da Ros, R; Pozzi, D; Brunelli, L; Cocconi, R
Abstract: Background: To prevent flu spread, Italian healthcare workers (HCWs) are annually recommended and given free flu vaccination. This measure of healthcare system protection resulted to be fundamental during COVID-19 pandemic to prevent staff shortage issue. Being the minimum coverage target set at 75%, we decided to evaluate vaccination adherence among HCWs at Udine University hospital. Methods: The 2020 vaccination campaign started 4 weeks earlier than usual and was based on a multiple offer strategy including a daily-dedicated clinic, in-ward administrations along with wide vaccination agenda promotion within hospital. The prevalence and the characteristics of vaccinated HCWs were compared with the same 2019 data. Results: During 2020, 1868 out of 3839 (48.7%) of HCWs were vaccinated, compared to 29.1% in 2019 (p < 0.0001). Doctors and residents were the most vaccinated categories in both years, being respectively 64.7% and 67.2% in 2020 vs 45.0% and 52.4% in 2019 (p < 0.0001). Midwives showed the best improvement in coverage passing from 44.4% to 20.4% (p = 0.0096). HCWs working in emergency areas and intensive care unit reached the highest adherence in 2020 (61.3%) and the best improvement compared to 2019 as well (37.9%; p < 0.0001). Conclusions: Even if the target was not reached, strategies adopted for 2020 vaccination campaign significantly increased HCWs adherence. COVID-19 contribution in this achievement cannot be ruled out, possibly representing a strong reinforcing element for HCWs awareness towards infectious disease prevention. Key messages: Despite the improvement in vaccination adherence, HCWs flu vaccination coverage still remains a concerning issue to be addressed. Increased flu shot adherence reached during COVID-19 pandemic should be not only a target to be maintained but even improved next year getting closer to herd immunity.